Harmonizing conscience claims and patient access to assisted death. Issue 3 (May 2023) - Wasylenko, Eric
The rights of patients to receive legally permissible interventions sometimes conflict with enshrined rights of providers to object, for reasons of conscience, to providing those interventions. Getting the balance right is challenging. But reasonable balance to manage these conflicting imperatives can be achieved in the design of programs for assisted death. Rather than limiting the discourse to the platform of competing individual rights, health leaders are urged to consider the broader societal benefits and impacts of valuing conscience in the practice of medicine, the creation of regulation and policy, and the delivery of healthcare. A method to determine that conscience claims are "genuine, " "reasonable, " and "acceptable" needs developing. A list of criteria toward this determination is offered.